Principles of the Feedback Action in Local Elements of Rail Yard Interaction - Yanovsky, Petro; Yanovska, Victoriia; Lytvynenko, Sergiy; Nesterenko, Halyna; Lytvynenko, Larysa (International Journal of Engineering and Technology, 2018)
Achievement of high-quality servicing level of cargo owners should be carried out under unconditionally effective use of rolling stock of railways and technical means. The real transport process should be implemented based on logistic cargo supply chains by types of connections for each shipment. The practice of railway operation shows that there is a significant shortage of train locomotives as a result of which the departure of ready trains at rail yard is often not carried out. In such cases, a feedback effect in local elements of interaction of these stations occurs. Due to delay in departure of trains, sending of already formed trains from rail yards is delayed; furthermore, because of the overflow of rail yard tracks, the sorting process on marshalling humps can be slowed down and delay of prepared trains for dismantling at arrival yard may occur. As a result of feedback action, downtimes of rail cars are increasing and movement of inventories is slowing down. In order to mitigate feedbacks effects in local elements of interaction, the principles of their operation, consideration of which will enable acceleration in passage of the rail car and cargo traffic through the railway network in practical activity, were formulated.Â Â